iTRAQ-based quantitative proteomic analysis of the antibacterial mechanism of silver nanoparticles against multidrug-resistant Streptococcus suis - Liu, Baoling; Liu, Dingyu; Chen, Tianbao; Wang, Xiaohu; Xiang, Hua; Wang, Gang; Cai, Rujian (Frontiers in Microbiology, 2023)
Background The increase in antibiotic resistance of bacteria has become a major concern in clinical treatment. Silver nanoparticles (AgNPs) have significant antibacterial effects against Streptococcus suis. Therefore, this study aimed to investigate the antibacterial activity and mechanism of action of AgNPs against multidrug-resistant S. suis. Methods The effect of AgNPs on the morphology of multidrug-resistant S. suis was observed using scanning electron microscopy (SEM). Differentially expressed proteins were analyzed by iTRAQ quantitative proteomics, and the production of reactive oxygen species (ROS) was assayed by H2DCF-DA staining. Results SEM showed that AgNPs disrupted the normal morphology of multidrug-resistant S. suis and the integrity of the biofilm structure. Quantitative proteomic analysis revealed that a large number of cell wall synthesis-related proteins, such as penicillin-binding protein and some cell cycle proteins, such as the cell division protein FtsZ and chromosomal replication initiator protein DnaA, were downregulated after treatment with 25 μg/mL AgNPs. Significant changes were also observed in the expression of the antioxidant enzymes glutathione reductase, alkyl hydroperoxides-like protein, α/β superfamily hydrolases/acyltransferases, and glutathione disulfide reductases. ROS production in S. suis positively correlated with AgNP concentration. Conclusion The potential antibacterial mechanism of AgNPs may involve disrupting the normal morphology of bacteria by inhibiting the synthesis of cell wall peptidoglycans and inhibiting the growth of bacteria by inhibiting the cell division protein FtsZ and Chromosomal replication initiator protein DnaA. High oxidative stress may be a significant cause of bacterial death. The potential mechanism by which AgNPs inhibit S. suis biofilm formation may involve affecting bacterial adhesion and interfering with the quorum sensing system.